Antibody Pressure by a Human Monoclonal Antibody Targeting the 2009 Pandemic H1N1 Virus Hemagglutinin Drives the Emergence of a Virus with Increased Virulence in Mice - Christopher D. O’Donnell (American Society for Microbiology, 2012)
ABSTRACT In 2009, a novel H1N1 influenza A virus (2009 pH1N1) emerged and caused a pandemic. A human monoclonal antibody (hMAb; EM4C04), highly specific for the 2009 pH1N1 virus hemagglutinin (HA), was isolated from a severely ill 2009 pH1N1 virus-infected patient. We postulated that under immune pressure with EM4C04, the 2009 pH1N1 virus would undergo antigenic drift and mutate at sites that would identify the antibody binding site. To do so, we infected MDCK cells in the presence of EM4C04 and generated 11 escape mutants, displaying 7 distinct amino acid substitutions in the HA. Six substitutions greatly reduced MAb binding (K123N, D131E, K133T, G134S, K157N, and G158E). Residues 131, 133, and 134 are contiguous with residues 157 and 158 in the globular domain structure and contribute to a novel pH1N1 antibody epitope. One mutation near the receptor binding site, S186P, increased the binding affinity of the HA to the receptor. 186P and 131E are present in the highly virulent 1918 virus HA and were recently identified as virulence determinants in a mouse-passaged pH1N1 virus. We found that pH1N1 escape variants expressing these substitutions enhanced replication and lethality in mice compared to wild-type 2009 pH1N1 virus. The increased virulence of these viruses was associated with an increased affinity for α2,3 sialic acid receptors. Our study demonstrates that antibody pressure by an hMAb targeting a novel epitope in the Sa region of 2009 pH1N1 HA is able to inadvertently drive the development of a more virulent virus with altered receptor binding properties. This broadens our understanding of antigenic drift. IMPORTANCE Influenza viruses accumulate amino acid substitutions to evade the antibody response in a process known as antigenic drift, making it necessary to vaccinate against influenza annually. Mapping human monoclonal antibody (hMAb) epitopes is a necessary step towards understanding antigenic drift in humans. We defined the specificity of an hMAb that specifically targeted the 2009 pH1N1 virus and describe a novel epitope. In addition, we identified a previously unappreciated potential for antibody escape to enhance the pathogenicity of a virus. The escape mutation that we identified with in vitro immune pressure was independently reported by other investigators using in vivo selection in nonimmune mice. Although in vitro generation of escape mutants is unlikely to recapitulate antigenic drift in its entirety, the data demonstrate that pressure by a human monoclonal antibody targeting a novel epitope in the hemagglutinin of the 2009 pandemic H1N1 virus can inadvertently drive the development of escape mutants, of which a subset have increased virulence and altered receptor binding properties.